EFFECT OF RARE EARTHS ON MECHANICAL PROPERTIES AND MICROSTRUCTURES OF SI3N4-BASED CERAMICS - Mu B.C.; Li M.; You X.Q.; Liu B.Y.; Gu Z.G.; Liu D.W. (My University, 2000)
The effects of Y2O3, La2O3 and Nd2O3 on the mechanical properties and microstructures of Si3N4-based ceramics were studied. It shows that a significant improvement in mechanical properties can be obtained by adding rare earths oxides in Si3N4. The fracture toughness and the flexural strength of Si3N4 added with both Y2O3 and La2O3 are 7.8 MPa·m1/2 and 962 MPa, respectively. The main reason is that adding rare earths in Si3N4 can improve the microstructure of the material and increase the aspect ratio of β-Si3N4 grain.